FAIM-L - SIVA-1: Two Modulators of XIAP in Non-Apoptotic Caspase Function - Coccia, Elena; Solé, Montse; Comella, Joan X (Frontiers in Cell and Developmental Biology, 2022)
Apoptosis is crucial for the correct development of the nervous system. In adulthood, the same protein machinery involved in programmed cell death can control neuronal adaptiveness through modulation of synaptic pruning and synaptic plasticity processes. Caspases are the main executioners in these molecular pathways, and their strict regulation is essential to perform neuronal remodeling preserving cell survival. FAIM-L and SIVA-1 are regulators of caspase activation. In this review we will focus on FAIM-L and SIVA-1 as two functional antagonists that modulate non-apoptotic caspase activity in neurons. Their participation in long-term depression and neurite pruning will be described in base of the latest studies performed. In addition, the association of FAIM-L non-apoptotic functions with the neurodegeneration process will be reviewed.